PERAN GURU SEBAGAI FASILITATOR PEMBELAJARAN DIGITAL DI ERA ABAD KE-21 - Muhammad Khoirul Amri Nst; Muhammad Yusuf Saifullah; Muhammad Arsyad (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2025)
The development of digital technology has brought fundamental changes to the global education system, including redefining the role of teachers in the classroom. This study aims to comprehensively examine how the role of teachers has transformed in the digital era using a literature review approach. The analysis was conducted on various scientific publications from accredited national and international journals in the period 2021–2025. The results of the study show that teachers no longer only act as transmitters of knowledge, but also as facilitators, mentors, innovators, and managers of digital learning environments. This role requires mastery of digital literacy, digital pedagogical skills, and adaptive readiness to dynamic technological changes. On the other hand, challenges such as limited infrastructure, digital access gaps, and low professional readiness are major issues that need to be addressed. This study recommends the need for education policies that support ongoing training and strengthening of teacher capacity so that they are able to play an optimal role in supporting 21st century learning. The results of this study are expected to provide theoretical and practical contributions to the development of digital education policies and strategies in Indonesia.